Intervenciones de enfermería y su relación con el estado psicológico de las adolescentes embarazadas que acuden al Centro de Salud Tipo A- Balzar de Vinces periodo octubre 2.018 – abril 2.019 - Sevillano Guerrero, Kevin Nelson (2019)
Adolescent pregnancies are a problem of great magnitude that has become a public health problem at both the international and national levels, they are associated with various antisocial behaviors and violence, due to the attitudes that young women take during pregnancy. teenagers feel several negative emotions like fear of reprobation in the face of the situation feeling lonely and helpless. That is why it is considered important that the nursing staff provide preventive care to this group of pregnant adolescents, through the dissemination of information to this age group, in order to provide security and protection to adolescents and can function in society improving their lifestyle. Formulating as a general objective to determine how nursing interventions influence the psychological changes of adolescents attending the Balzar de Vinces Health Center - Period October 2018-April 2019. In the research, a field study was carried out, descriptive and transversal, using two types of inductive, deductive, statistical methods, applying the quantitative and qualitative modality. They obtained as a result that pregnant adolescents mostly do not have the support of their families, generating feelings of anguish, fear, and sometimes feel discriminated by society, manifesting in greater quantity that they are not able to assume the role of mothers, evidencing that they do not know the different physical, psychological and biological changes that can be faced during this stage, which the nursing staff as a whole does not provide the necessary information on the states that these pregnant adolescents will face.